2019
DOI: 10.1093/femsec/fiz199
|View full text |Cite
|
Sign up to set email alerts
|

Host tree organ is the primary driver of endophytic fungal community structure in a hemiboreal forest

Abstract: Despite numerous studies on plant endophytes, little is known about fungal communities associated with different aboveground tissues of living trees. We used high-throughput sequencing to compare the diversity and community structure of fungi inhabiting leaves, branches and trunks of Alnus incana and Corylus avellana growing at three hemiboreal forest sites. Our analysis revealed that tree organs are the main determinants of the structure of fungal communities, whereas the effects of host species and locality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 68 publications
1
20
0
1
Order By: Relevance
“…(Ragazzi et al, 2003). In a comparison of gray alder (Alnus incana) and hazel (Corylus avellana) (Küngas et al, 2020), further concluded that tree organs are the main determinants of fungal community structure, whereas the effect of host species and locality appears less important. In addition, tree health may also play a role (Berg et al, 2017).…”
Section: Discussion Organ Rather Than Growth Site Determines the Beech Microbiomementioning
confidence: 96%
“…(Ragazzi et al, 2003). In a comparison of gray alder (Alnus incana) and hazel (Corylus avellana) (Küngas et al, 2020), further concluded that tree organs are the main determinants of fungal community structure, whereas the effect of host species and locality appears less important. In addition, tree health may also play a role (Berg et al, 2017).…”
Section: Discussion Organ Rather Than Growth Site Determines the Beech Microbiomementioning
confidence: 96%
“…Given that hosts exist within external environments, external host habitats are much more complex in terms of scale, abiotic heterogeneity and C resources, compared with internal host habitats. Thus, environmental microbiomes – and to a lesser extent external host microbiomes – likely experience greater exposure to migrations of different organisms/genes, leading to a greater variety of niches suitable for the establishment of a larger variety of organisms compared with internal host habitats (Pent et al ., 2017; Küngas et al ., 2020). Different abiotic factors such as pH, climate and organic matter contents shape the environmental community compositions of bacteria and fungi (Tedersoo et al ., 2014; Louca et al ., 2016; Bahram et al ., 2018; Delgado‐Baquerizo et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This result is in agreement with previous studies suggesting organ-specificity of fungal endophytes in olive tree ). As previously suggested for other woody species (Küngas et al, 2020), it is likely that the growth of endophytes in olive is restricted by the features of a particular organ.…”
Section: Discussionsupporting
confidence: 54%
“…Plant genetics (at species or genotype level) also control endophytic fungal communities' composition of woody perennials Lamit et al, 2014;Bálint et al, 2015;Yao et al, 2019;Küngas et al, 2019). As far as we known, host plant effect on fungal assemblage have been recognized only on endophytes colonizing leaves Yao et al, 2019), roots (Andrade-Linares and Franken, 2013) and…”
Section: Introductionmentioning
confidence: 99%